An Approach to Neutrosophic Subrings - Vildan Çetkin; Halis Aygün (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The purpose of thispaper is to observe some algebraic structures of a single valued neutrosophicset. For this reason, we introduce a new notion which is called a neutrosophicsubring by combining the ring structure and neutrosophic sets. Then weestablish some fundamental properties and characterizations of the proposednotion.